Physical fitness and cardiovascular endurance status of Iranian elite female taekwondo athletes - Dadgostar, H.; Ghanbarnasab, M.; Nazari, A. (Asian Journal of Sports Medicine, 2020)
The present study aimed to determine the anthropometric indices and aerobic and cardiopulmonary capacity of Iranian elite female taekwondo athletes and also to investigate the relationship between the anthropometric indices and the cardiopulmonary capacity of this group of athletes at national and championship levels. For this purpose, 33 elite female taekwondo athletes (12 at national and 21 at championship levels) participated in this study. The body fat percentage was measured by body impedance analyzer, and cardiopulmonary evaluation was performed using an incremental exercise test. Mean height, BMI (body mass index), and the body fat percentage were determined as 169.86 ± 6.74 cm, 20.89 ± 2.57 kg.m-2, and 22.54 ± 5.44%, respectively. The rates of VO2max and VO2@AT% in the Cardiopulmonary Exercise testing (CPET) were 48.95 ± 7.11 mL/kg.min and 60.43 ± 6.43%, respectively. Correlation results showed that VO2max was negatively correlated with the body fat percentage (r = -0.50, P = 0.003), BMI (r = -0.40 P = 0.02), and weight (r = -0.35, P = 0.044). Furthermore, it was found that the age factor was negatively correlated with HRMAX in CPET test (r = -0.46, P = 0.007) and exercise hours per week (r = -0.37, P = 0.031). The findings of this study revealed that the rate of VO2max, as the index of aerobic capacity among elite female taekwondo athletes, was about 50 mL/kg.min. Normal BMI, which was similar to that of the other taekwondo elites in the world, and an acceptable body fat percentage were reported in our study, while the body fat percentage was relatively higher than that of the other elite female taekwondo athletes in the world.